Internalisasi Nilai Disiplin Ibadah dalam Pembelajaran PAI di SMK Ma’arif 8 Kebumen - Irodati, Fibriyan (Prodi Pendidikan Agama Islam IAINU Kebumen, 2022)
Discipline of worship is a good value recommended in Islamic religious teachings. Islam always recommends to always be disciplined and istikomah in carrying out worship, both obligatory and sunnah worship. Internalizing the discipline of students' worship in PAI learning is something that must be done by every PAI teacher and school, including SMK Ma'arif 8 Kebumen. Departing from the reality of learning at Ma'arif 8 Kebumen Vocational School as a formal educational institution that has experienced significant development, it can be seen from the internalization of the values of religious discipline in effective learning by touching the impact of learning (instructional effect) without leaving the accompanying effect (nurturant effect). This is integrated with always increasing the role of Islamic religious education in an effort to foster the character ofthe discipline of worship in students at school. This study aims to describe and analyze the internalization of the values of the discipline of worship in PAI learning at SMK Ma'arif 8 Kebumen. This research is a qualitative research, taking the background of SMK Ma'arif 8 Kebumen. Data collection was carried out in this study using several methods, namely: observation, interviews, and documentation. Data analysis was carried out by qualitative analysis, while checking the validity of the data was carried out by conducting triangulation. The results of the study show that Ma'arif 8 Kebumen Vocational High School in the process of internalizing thediscipline of worship, its students use several strategies. The strategies used are appreciation, motivation, and habituation. The teacher carries out an appreciation strategy with several mutually sustainable stages, namely the stages of providing understanding or information, modeling and applying the values of the discipline of worship. The teacher carries out a motivational learning strategy by motivating students that the discipline of worship is something that must be applied in the life of Muslims. The habituation strategy is also the key to the success of internalizing students' religious discipline.